Investigated of Desalination of Saline Waters by Using Dunaliella Salina Algae and Its Effect on Water Ions - Asma Moayedi; Bahman Yargholi; Ebrahim Pazira; Hossein Babazadeh (Salehan Institute of Higher Education, 2019)
Nowadays, due to augmentation of population and expansion of cities and the limitation of fresh water sources in the world, existing water resources cannot meet the human needs. Desalination or reduction of salinity of water through biological methods involves the use of plant species, microorganisms, algae or a combination of them, which can be effective in reducing water salinity. The objective of this study was to investigate the desalination of saline waters by using Dunaliella salina algae. For this purpose, the experiments were carried out as factorial based on completely randomized design. The expected tests were conducted in a laboratory controlled condition for humidity, light and temperature (90 days). During this research, the Electrical Conductivity (EC) was measured daily. The results showed that salt absorption in Dunaliella salina algae was significantly different. High salt absorption was observed in Dunaliella salina at a concentration of 130mS.cm-1. Due to the constant humidity, light and temperature, salt removal from saline water was observed in laboratory conditions. The results of this study indicate that significant reduction of chlorine, sodium and bicarbonate levels were observed using Dunaliella salina algae. According to the results of this study, it seems that reducing salt absorption in algae is due to the use of salt in the metabolism and the growth and proliferation of algae. The absorption process in this study showed that the catch of Dunaliella salina has a good ability to remove salt and can be used as an appropriate suggestion for salt removal from saline water.